PT1 & PT2 Architecture drawing (RFA-528_Rev B) - WOHA Designs PTE LTD; BUCG-ABC Joint Venture; Web Structures (Brac University, 2023)
This record contains architectural contractor shop drawings of Brac University New Campus Project. It consists of both PDF and DWG version of drawings.